General requirements for teacher training in the organization of pedagogical master classes - Ochilov Og’abek Narzullayevich (Zien Journals, 2022)
The article describes the general requirements for the content of the lesson in the organization of master classes, the didactic purpose, objectives, content and methods of organizing lessons
Keywords: general requirements; educational requirements; didactic requirements; hygienic requirements.